Multidisciplinary design optimization on the splitter blade of high head Francis turbine - Song, Y H; Guo, P C; Sun, L G; Zhou, H T; Luo, X Q (IOP conference series. Earth and environmental science, 2018)
Hydraulic and structural performances are two main subjects in the optimization design of hydraulic machines. This article gives consideration to both hydraulic and structural performances during the optimization process of hydraulic turbine with main and splitter blades on the basis of Multidisciplinary Design Optimization (MDO). The aim is to improve the optimization methods of hydraulic turbine, shorten the development cycle time and ensure stable and efficient operation of the unit. Computational fluid dynamics(CFD) and finite element method(FEM) analysis are combined to improve the overall performance of the runner in the multidisciplinary optimization process. The optimization considers the whole runner including the crown and band to get more accurate results of stress distribution. Open Grip program was used to parameterize runner blade and Bezier curve was used to match the bone line and it changed the blades through transforming the bone lines of different profile. NSGA-II algorithm was adopted during the optimization calculation. What's more, super transfer approximation method was used to obtain the weighted coefficients considering the overall performance under three operating conditions, based on this, the final optimization result was obtained. The whole performance of optimized runner gets improved and has a better outflow quality. Also, it provides a feasible method for engineering application in the multidisciplinary optimization design of runner blades.